Kebijakan Social Protection Floor Pemerintahan Jepang dalam Menangani Dampak Fenomena Global Hikikomori - Irwan, M.J. Rinal; Asy'ari, Muh.; Tas'an, Ayu Kartika Julianingsih (Journal of International and Local Studies, 2025)
Japan image that rich of culture and its technological advancement still face a social withdrawal issue that is hikikomori which now widely considered as a global issues. More than 1.4 million of its citizens contribute to multiple problem and negative impact from social isolation, school attendance, and unemployment. This calls for action towards hikikomori. This research reviews Japan policies towards hikikomori issues qualitively, through the global context using ILO’s global framework social protection floor as “lens” to analyze Japan social protection policies that valid in 2016-2024 towards hikikomori impact and problem. Based on its general policy, Japan has the 4 basic component of SPF, with the specific policies toward hikikomori has social services policies as the majority. But its policy coverage tendecy still leaning toward domestic , and some limited aspect in its general policies towards Japanese impact and its issues.